Product Development from Reused Cans: A Profit-Oriented Training Program for MSMEs in Tanjung Duren, West Jakarta - Menul Teguh Riyanti; Ariani; Layla Nurina Kartika Iskandar; Januar Ivan; Tiara Hanjani Putri Nugroho; Tulus Hambawan (Universitas Muhammadiyah Palembang, 2025)
The issue of inorganic waste, such as used cans, is increasingly prevalent in urban environments, including in the Tanjung Duren area of West Jakarta. Used cans, specifically large-sized paint cans, can be reused to create new products with both economic value and practical functionality. However, micro, small, and medium enterprise (MSME) actors, particularly women in the area, still lack the practical skills needed to process such waste creatively. In response to this need, the Faculty of Art and Design (FSRD) of Trisakti University organized a Community Engagement Program in the form of a training on reusing used cans to produce economically valuable items. This activity was attended by ten women MSME participants and was carried out using demonstration and hands-on mentoring methods. The outcome of the training was the creation of ten innovative products in the form of multifunctional storage containers that also serve as stools. This program not only offers a solution to environmental problems but also opens new economic opportunities for the participating community members.